WA1ms: A 2.61 Ga muscovite standard for 40Ar/39Ar dating - Jourdan, Fred; Frew, Adam; Joly, A.; Mayers, C.; Evans, Noreen (Pergamon, 2014)
The 40Ar/39Ar dating technique requires the use of neutron fluence monitors (standards) to allow calculation of the age of a sample. Precise calibration of these standards is crucial to obtaining accurate ages and decreasing the uncertainties associated with 40Ar/39Ar dates. Few fully intercalibrated 40Ar/39Ar standards with a sufficient total fusion grain-to-grain reproducibility are currently in use in the argon community. For Precambrian samples, only Hb3gr hornblende (~1.08 Ga) yields sufficient grain-to-grain reproducibility and has an appropriate age for acceptable argon isotopic ratio measurements. Here, we present chemical and intercalibration results for a new ~2.61 Ga standard. WA1ms is a muscovite extracted from an Archaean shear zone in the Lake Johnston greenstone belt, Western Australia. In situ trace element analysis by ELA-ICPMS revealed consistent K contents, subtle zonation and intra-grain and grain-to-grain heterogeneities in Rb, Sr, Ti, and Fe but a lack of mineral inclusions. WA1ms has been investigated over 3 irradiations ranging from 25 to 40 h, in two reactors, with several disc positions and three grains sizes and has been calibrated against FCs and GA1550, and Hb3gr. Overall, we carried out 48 total fusion and 4 step-heating experiments of WA1ms crystals. Flat age spectra and average F-value (40Ar*/39ArK) relative standard deviations ranging from of 0.43% to 0.60% (P = 0.15–0.83) for 47/48 analyses demonstrate the reproducibility of WA1ms and its suitability as a reliable 40Ar/39Ar standard.We calculated R[WA1ms/FCs] = 205.59 ± 0.25, R[WA1ms/GA1550] = 57.25 ± 0.06 and R[WA1ms/Hb3gr] = 3.9713 ± 0.014 (all with P > 0.14) allowing direct comparison between WA1ms and any standards in used in the community, provided that they have been calibrated against any of the three standards used in the calibration and regardless of the age adopted for each of these standards. The recently revised decay constant values and standard ages proposed by Renne et al. (2011) yield a weighted mean age of 2614.2 ± 1.5 Ma (±0.055%; P = 0.8; 1σ) for WA1ms against the three standards. When calibrated solely against FCs in order to minimize correlated errors between FCs vs. GA1550 and Hb3gr, we calculate a preferred age of 2613.0 ± 2.4 Ma (±0.09%) which is recommended when using this standard. Additionally, this corresponds to a 40Ar*/40Kvalue of (0.3375 ± 0.0057) 10–1 for WA1ms, which is independent of the value of the decay constant used for calculation and allows recalculation of the age of WA1ms for any preferred set of decay constants and standard ages. Using the constants proposed by Steiger and Jäger (1977) directly calculated from the three R-values, yields an age of 2598.2 ± 3.5 Ma corresponding to an identical, although less precise 40Ar*/40K value of (0.3375 ± 0.0086) x 10–1. Benefits of this standard include: (1) an increased relative precision per crystal analyzed relative to other standards for Proterozoic and Archaean samples, (2) no post-irradiation waiting time due to the absence of Ca (no need to wait for 37ArCa decay), and (3) loading of standard grains that are optically different from the unknown (e.g., pyroxene or hornblende) to avoid standard-unknown mixing. WA1ms is freely available to the 40Ar/39Ar community.